Food Security in the Drylands of South Asia and Sub-Saharan Africa: Research Challenges and Opportunities - Nkonya, Ephraim; Shiferaw, Bekele; Msangi, Siwa (Annals of Arid Zone, 2016)
Despite the significant agricultural research achievement that led to the green revolution, South Asia (SA) and Sub-Saharan Africa (SSA) remain the hotspots of food and nutrition insecurity in the world. One of the reasons behind this challenge is the failure of the green revolution to increase dramatically rain fed crop and livestock productivity in SA. The green revolution achievement has also generally eluded SSA despite the increased availability of high-yielding and risk-reducing cultivars and agricultural innovations. Many factors are attributable to the lack of productivity growth. This paper investigates the major factors that have contributeq to the food insecurity in SA and SSA and forecasts the future of the food production' and consumption and their effect on food and nutrition security to the year 2020. Our projections. of food production and consumption show that child malnutrition in SA is decreasing much faster than the case in SSA, due to increase in per capita income, female education and female life expectancy. Fast reduction in child malnutrition is also possible in SSA if the countries invest significantly in improvement in agricultural production and in addressing the constraints that impede access to food. The demand for livestock products has been increasing dramatically mainly due to increasing income and urban population. The livestock sector also has a large potential to achieve food and nutrition security in the drylands. Unfortunately, past research and development investments in livestock have not reflected the potential and opportunities offered by the sector. Harnessing the potential of livestock would require developing suitable crop-livestock innovations to improve productivity. Even though returns to agricultural research investments have been high and have shown a great potential to increase food security in both SA and SSA, government and donor research funding has generally decreased in the SSA region where national capacity is weak and underdeveloped. There is an urgent need to increase availability of funds to address the research challenges .and harness the opportunities. in the two regions. Returns to the research investment. will also have multiplier effect on reducing food and nutrition insecurity if the support services - such as extension services, market services, etc. are developed:, Research also need to take seriously farmer innovations, which have shown great potential in developing technologies well adapted to the, drylands. Key words: Food security, drylands, child malnutrition, access to food, South Asia, Sub-Saharan Africa.